2023
DOI: 10.3389/fpsyg.2023.1078874
|View full text |Cite
|
Sign up to set email alerts
|

Different personality factors drive work and non-work creativity

Abstract: This study examined whether creativity at work and outside of work had the same (or different) Big Five personality antecedents. Results revealed that although self-reported personal creativity outside of the workplace was related to the Openness to Experience trait only, supervisor-rated work creativity was associated with Openness, Extraversion, and Conscientiousness, and that after controlling for the effects of Extraversion and Conscientiousness, Openness did not contribute incremental validity in predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…As emotionally stable individuals are self‐confident and feel comfort in different settings, the trait is generally associated with calmness and safety and high emotional stability, and this makes individuals more open to participating in creative endeavors (Sung & Choi, 2009; Tsai, 2016). Although some studies (Shaw & Yu, 2023; Sung & Choi, 2009) showed no conclusive link between emotional stability and creativity, others identified supportive connections (Esfahani et al, 2012; Strong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…As emotionally stable individuals are self‐confident and feel comfort in different settings, the trait is generally associated with calmness and safety and high emotional stability, and this makes individuals more open to participating in creative endeavors (Sung & Choi, 2009; Tsai, 2016). Although some studies (Shaw & Yu, 2023; Sung & Choi, 2009) showed no conclusive link between emotional stability and creativity, others identified supportive connections (Esfahani et al, 2012; Strong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%